Some Coincidence and Common Fixed Point Theorems for Two Pairs of Self-Mappings Satisfying a Rational Inequality in Complex Valued Metric Spaces (Journal of Informatics and Mathematical Sciences, 2021)
In this paper, we prove some coincidence and common fixed point theorems for two pairs of weakly compatible mappings satisfying a rational inequality in the framework of complex valued metric spaces. The proved results generalizes and extends some well known results in the literature.
Keywords: Complex valued metric spaces; Common fixed point; Weakly compatible